Interpreting the Gospel of John in Antioch and Alexandria - DeCock, Miriam (Atlanta Society of Biblical Literature, 2020)
Cover -- Contents -- Abbreviations -- Introduction -- 1. John, His Gospel, and Its Interpretation in the Schools of Alexandria and Antioch -- 2. The Cleansing of the Temple of John 2 -- 3. The Samaritan Woman at the Well of John 4 -- 4. The Healing of the Man Born Blind of John 9 -- 5. The Good Shepherd Parable of John 10 -- 6. The Resurrection of Lazarus of John 11 -- Conclusion -- Bibliography -- Ancient Sources Index -- General Index.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books